Electroacupuncture for the treatment of functional dyspepsia: A systematic review and meta-analysis. Issue 45 (6th November 2020) - Mao, Xinyong; Guo, Song; Ni, Wenchao; Zhang, Tao; Liu, Qian; Du, Sijing; Luo, Mengxue; Pan, Yuyan; Wu, Baoqi; Su, Xiaolan; Yang, Yang; Guo, Yu; et al.
Abstract: Background: Functional dyspepsia (FD) is a common functional gastrointestinal disease. Acupuncture, including electroacupuncture (EA) is widely used as a complementary and alternative treatment for patients with FD. This study aimed to explore the effectiveness of EA for the treatment of FD. Methods: We searched Embase, PubMed, and the Cochrane Central Register of Controlled Trials (Cochrane Library) for randomized controlled trials of FD treated by EA from inception to February 3, 2020. Two reviewers will independently screen studies for data extraction and assess the quality and risk of bias. The Cochrane Collaboration's risk of bias tool, RevMan 5.3 software were used for meta-analysis. Data were pooled to calculate relative risk and 95% confidence intervals (CIs) of substantial improvement after treatment for dichotomous data and mean differences (SMDs) and 95% CIs for continuous data. Results: Seven randomized clinical trials included 853 patients. This meta-analysis investigated the effectiveness of EA alone in the treatment of FD relative to sham-EA or pharmacologic medication (PM). The results showed that EA could significantly improve clinical symptoms. Compared with sham-EA, EA was more effective in reducing symptom scores (SMD −3.44, 95% CI −4.21 to −2.67) and increasing normal slow waves of electrogastrogram (SMD 0.93, 95% CI −0.30 to1.55). When EA was combined with PM, there was no significant difference in reducing symptom scores (SMD −0.18, 95% CI −0.51 to 0.16), increasing the effective rate of clinical symptoms (risk ratio 1.04, 95% CI 0.96 to 1.13), enhancing the level of plasma motilin (SMD 0.93, 95% CI −0.30 to1.55), and reducing gastric half-emptying time (SMD 0.02, 95% CI −0.16 to 0.20). The results also showed that there were very few adverse events reported. Conclusion: This meta-analysis suggests that EA is better than the placebo (sham-EA) in treating FD, and the therapeutic effect of EA on FD is equivalent to that of PM on FD. Compared with PM, EA for FD is safer and has fewer adverse reactions. Despite limitations due to the quality and number of the included studies, EA might be used as an effective and safe treatment for FD.